Avaliação da ansiedade de mães de crianças confirmadas para Covid-19 no primeiro ano de vida - Fontenele, Nágila Lima (2023)
The experience of stressful events, such as the Covid-19 pandemic, impacts directly on the mothers’ mental health, and may increase their anxiety levels, especially in relation to the concern for the well-being and safety of children who are also susceptible to the disease. The objective was to evaluate the anxiety levels of mothers with children confirmed for Covid-19 in the first year of life. This was a descriptive, cross-sectional study with a quantitative approach, carried out in the city of Fortaleza/CE-Brazil. The sample consisted of 31 mothers of children confirmed for Covid-19 in the first year of life notified in the eSUS epidemiological surveillance system from February 2020 to January 2021, the inclusion and exclusion criteria were respected. Data collection took place from May to July 2023, by telephone contact, with the application of a form to identify mothers’ sociodemographic and epidemiological variables, child’s sociodemographic, epidemiological and clinics variables. To assess maternal anxiety levels, the State-Trait Anxiety Inventory (STAI) was applied, using the anxiety classification: Percentile < 25 (low anxiety): STAI – Trait (scores from 23 to 35) and STAI – State (scores from 22 to 35); 25th to 75th percentile (moderate anxiety): STAI – Trait (scores from 36 to 62) and STAI – State (scores from 36 to 53); Percentile > 75 (high anxiety): STAI – Trait (scores from 63 to 69) and STAI – State (scores from 54 to 63). For data analysis, the IBM® SPSS® Statistics version 29 program was used. To verify the association between the variables, the Fischer-Freeman-Halton Exact test was used. 95% confidence interval (CI=95%) was used, considering statistically significant relationships with a significance level of 5% (p< 0.05). Study approved by the ethics and research committee of the Federal University of Ceará. There was a predominance of mothers aged > 30 years (51.6%; 31.1± 7.1), brown (70.9%), married (51.6%), with higher education (41.9%), with income between one and two minimum wages (45.2%), coming from regional VI (45.2%). It was prevalent mothers who were confirmed for Covid-19 (70.9%), the most performed test was RT-PCR (32.3%) and the rapid test (32.3%) and the majority (51.6%) had Covid-19 at the same time as their child. As for the children, predominated age > 7 months (67.7%; 10.8±7.3), female (54.8%) and residents in the VI region (45.2%). The presence of symptoms was more identified (67.8%), the most common being fever (51.6%), rapid test (64.5%), absence of hospitalization (83.9%) and laboratory closure criterion (100.0%). The participants showed more moderate anxiety (percentile between 25 and 75) both for the STAI - Trait (45.2%) and for the STAI-State (51.6%). There was statistical significance between education and the STAI-Trait scale (p=0.033), education and the STAI-State (p=0.032) and income and the STAI-State (p=0.034) with high anxiety. It was concluded that mothers had moderate and high levels of anxiety in the context of children confirmed with Covid-19. In addition, factors such as education and income have been described as having direct relationships with maternal anxiety levels.